Ethnosemiotic Analysis of Verbal and Nonverbal Symbols in Torompio Traditional Dance of the Pamona Ethnic Group, Central Sulawesi - Meilyn Wowor; Syamsuddin Syamsuddin; Agustan Agustan; Ida Nuraeni (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the verbal and nonverbal symbols in the Torompio traditional dance of the Pamona ethnic group in Central Sulawesi. It seeks to interpret the cultural meanings embedded in its movements, lyrics, costumes, and music through an ethnosemiotic approach to reveal the moral, social, and spiritual values reflected in the dance. Methodology: This study employed a qualitative descriptive method with an ethnosemiotic approach, integrating ethnography and semiotics. Data were collected through observation, semi-structured interviews, and documentation using audio-visual tools such as cameras and recorders. Supporting data were analyzed using an interactive model of data reduction, display, and conclusion drawing with reference to Miles and Huberman. Main Findings: The study found that verbal symbols in the Torompio dance such as traditional chants and lyrics express love, respect, and harmony, while nonverbal symbols such as gestures, movements, costumes, and colors represent unity, spirituality, and cultural identity. These symbols together form a semiotic system reflecting Pamona philosophical values of balance, modesty, and social harmony in human relationships and cultural life. Novelty/Originality of this study: This study offers a new ethnosemiotic interpretation of the Torompio traditional dance, highlighting its dual role as an artistic performance and a medium of cultural communication. By revealing how verbal and nonverbal signs convey moral, spiritual, and social meanings, it advances understanding of Indonesian traditional arts as living semiotic systems that preserve local wisdom and identity.